Watta Satta: Bride Exchange and Women's Welfare in Rural Pakistan - Jacoby, Hanan G; Mansuri, Ghazala (American Economic Review, 2010)
Can marriage institutions limit marital inefficiency? We study the pervasive custom of watta satta in rural Pakistan, a bride exchange between families coupled with a mutual threat of retaliation. Watta satta can be seen as a mechanism for coordinating the actions of two sets of parents, each wishing to restrain their son-in-law. We find that marital discord, as measured by estrangement, domestic abuse, and wife's mental health, is indeed significantly lower in watta satta versus “conventional” marriage, but only after accounting for selection bias. These benefits cannot be explained by endogamy, a marriage pattern associated with watta satta. (JEL J12, J16, O15, O18, Z13)